Mengintip Sistem Pendidikan di Negara Termaju di Dunia. - Zidan Fernando; Dion Dwy Saputra; Wawan Saputra (Journal of Information Systems and Management (JISMA), 2024)
The aim of the education system is to educate the life of the nation and also to develop the whole human being. This report uses a descriptive qualitative method by taking notes because the source was taken by listening to the oral narrative from the GURU GEMBUL YouTube channel entitled "A Peek into the Education System in the Most Developed Countries in the World". The goal is to develop an education system to improve the quality of life of the population. Belief in the importance of education which can change human civilization towards the formation of an educational system is felt to be a means for achieving educational goals. The increasing development of science and technology in various countries with different levels of development indirectly influences the development of the education system in each country.